Clashes of knowledge: orthodoxies and heterodoxies in science and religion - Meusburger, Peter; Welker, Michael; Wunder, Edgar (Knowledge and space, 2008)
Do traditional distinctions between 'belief' and 'knowledge' still make sense? How are differences between knowledge and belief understood in different cultural contexts? This book explores conflicts between various types of knowledge, especially between orthodox and heterodox knowledge systems, ranging from religious fundamentalism to heresies within the scientific community itself. Beyond addressing many fields in the academy, the book discusses learned individuals interested in the often puzzling spatial and cultural disparities of knowledge and clashes of knowledge.